The utilization of rapid serological tests in COVID-19 diagnostics - a high risk of false-negative results in outpatient care, with particular emphasis on dental treatment - Monika Tysiąc-Miśta; Sylwia Bulanda (Nofer Institute of Occupational Medicine, 2021)
In order to mitigate the spread of COVID-19, in the early stages of the pandemic outbreak, postponing elective procedures was recommended all around the world. Outpatient care and dental care were limited to telephone advice and emergency services. Dental staff is particularly vulnerable to SARS-CoV-2 contraction, because of the inevitable contact with patients' body fluids during aerosol-generating procedures. The implementation of diagnostic tests among ambulatory patients could improve the occupational safety among outpatient care personnel. The aim of this review was to introduce information regarding COVID-19 diagnostics with a particular focus on the methods which can be utilized in an outpatient and dental care setting. An online PubMed database review of articles on COVID-19 diagnostics, published on February 12-May 15, 2020, was conducted. Reverse transcription polymerase chain reaction is the gold standard in COVID-19 diagnostics, which determines if a person has an active infection. Unfortunately, its utilization in outpatient care is limited. Serological enzyme-linked immunosorbent assays identify people who were infected, including those who have had an asymptomatic infection, but they do not give sufficient information about the acute infection. Rapid serological assays developed to facilitate testing outside of laboratories, especially in dental offices, are not recommended by the World Health Organization to be used outside research settings, and they should not constitute the basis for clinical decision-making because of frequent false-negative results which may consequently contribute to personnel infections. Out of all available COVID-19 diagnostic methods, rapid serological assays seemed to be a method of choice in outpatient medical care. Unfortunately, their results turned out to be unreliable. The best methods to ensure the occupational safety of medical staff and to avoid cross-infections in outpatient care facilities include a thorough epidemiological interview, temperature measurement to rule out patients with an active infection, and the implementation of strict infection control procedures. Med Pr. 2021;72(2):155-62